The role of physical exercise in diseases treated with colchicine - an ancient drug with novel clinical applications - Rejdych, Julia; Podyma, Katarzyna; Rosołowska-Żak, Sara; Sambura, Maria; Sas, Wiktoria; Ryznar, Gracja; Pierzchała, Piotr; Minkowska, Michalina; Chimiak, Krystyna; Bylica, Gabriela (Quality in Sport, 2024)
Colchicine, a lipid-soluble alkaloid derived from Colchicum autumnale, has a long history of use dating back to ancient Egypt. Traditionally used to alleviate pain and swelling, colchicine is now administered for various diseases, including gout and Familial Mediterranean Fever (FMF). Recent studies have expanded its applications to atherosclerotic cardiovascular diseases, such as acute coronary syndromes and COVID-19. This review aims to summarize the diverse clinical applications of colchicine, with a particular focus on its role in athletes and the synergistic effects of physical exercise in these conditions. Colchicine exhibits broad anti-inflammatory effects primarily by disrupting microtubule functions, which impairs neutrophil migration and reduces cytokine production. Despite its narrow therapeutic window and potential for drug interactions, colchicine is considered safe and effective for managing conditions like gout, FMF, and acute coronary syndromes. Physical exercise complements colchicine treatment by enhancing symptom control and disease management. However, the role of colchicine in COVID-19 treatment remains inconclusive, necessitating further research.